2020
DOI: 10.1177/1550147719900109
|View full text |Cite
|
Sign up to set email alerts
|

Studying on the design and simulation of collision protection system between vehicle and pedestrian

Abstract: Pedestrian protection technology has become the most important issue in the field of vehicle safety. The design and simulation method of pedestrian protection system for vehicles is studied based on the Teoriya Resheniya Izobreatatelskih Zadatch theory in this article. The optimal solution of a new type of all-around airbag system mounted to the front of vehicles is presented after performing some Teoriya Resheniya Izobreatatelskih Zadatch analysis tools, such as the component analysis, causal analysis, resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In urban areas in particular, pedestrians and traffic volumes are large, and past reports have shown that important risk factors related to pedestrian crash risk include the number of bus stops per unit time, parking spaces, crosswalks, frequency of violations, variations in traffic speed, and number of intersecting side roads, in addition to through and intersecting traffic volumes [29] The design of roadways and the development of various land uses can both increase and decrease pedestrian traffic crash injuries, and urban and regional planners need to design the built environment to minimize pedestrian risk [30]. Widespread use of automatic braking systems to reduce the speed of vehicles in collisions could also reduce serious traffic trauma for pedestrians [31]. Severe traffic trauma while walking was particularly high in this study, especially among 0-5 and 6-11 year-olds, and interventions will have to be made to encourage safe pedestrian behavior in the patients themselves and their families [32].…”
Section: Discussionmentioning
confidence: 99%
“…In urban areas in particular, pedestrians and traffic volumes are large, and past reports have shown that important risk factors related to pedestrian crash risk include the number of bus stops per unit time, parking spaces, crosswalks, frequency of violations, variations in traffic speed, and number of intersecting side roads, in addition to through and intersecting traffic volumes [29] The design of roadways and the development of various land uses can both increase and decrease pedestrian traffic crash injuries, and urban and regional planners need to design the built environment to minimize pedestrian risk [30]. Widespread use of automatic braking systems to reduce the speed of vehicles in collisions could also reduce serious traffic trauma for pedestrians [31]. Severe traffic trauma while walking was particularly high in this study, especially among 0-5 and 6-11 year-olds, and interventions will have to be made to encourage safe pedestrian behavior in the patients themselves and their families [32].…”
Section: Discussionmentioning
confidence: 99%
“…This includes vehicle design and safety assessments (e.g. Lu et al, 2020; Wu et al, 2020), search and rescue tools (e.g. Coppini et al, 2016), pressurised water pipe failure (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In an all around planned vehicle, the body and different parts are the defensive layer for the tenants of the vehicle. The accessibility of elite execution PCs and crash reproduction programming has upset the interaction (7). Mishap crash insights, biomechanics, unofficial laws, and public area front facing security tests will be surveyed (8).…”
Section: Literature Surveymentioning
confidence: 99%